Implementation of the Village Zakat Index in the Moncongloe Lappara Village Community, Moncongloe District, Maros Regency - Ummy Aisyah Arsyad; Rahman Ambo Masse; Trisno Wardy Putra (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
This Study aims to determine the priority scale regarding the eligibility of Moncongloe Lappara village to receive zakat funds. This study uses a mixed method research approach, which combines qualitative and quantitative methods. Quantitative data was obtained through IDZ measurements based on five main dimensions: economy, education, health, social, and da'wah, while qualitative data was collected through in-depth interviews and direct observation of the social conditions of the community.The IDZ calculation results obtained by the researcher in Moncongloe Lappara Village were 0.57, which is classified as “fairly good.” The details of each dimension index are as follows: the economic dimension scored 0.38. The health dimension scored 0.67, the education dimension scored 0.75, the social dimension scored 0.60, and the da'wah dimension scored 0.54. This shows that Moncongloe Lappara Village can be considered or has the opportunity to receive assistance from zakat funds, especially to improve the welfare of villagers in terms of economy. The main program recommendations prioritized for implementation in the Moncongloe Lappara Village community are the establishment of an integrated creative industry community, the provision of a flea market, the provision of a sharia cooperative or other types of financial institutions, assistance, and financing for MSMEs.